Karakterisasi Contoh Spontan Guru Pemula Dalam Pembelajaran Matematika - Selly Meinda Dwi Cahyaningsih; Subanji Subanji; I Made Sulandra (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: The purpose this study is to explore characterization of teacher's spontaneous example. Type a study is deskriptif kualitatif, subject is beginner teacher. The results show that three spontaneous examples characterization of beginner teacher such that illustrative spontaneous examples, clarified spontaneous examples, and confirmatory spontaneous examples. Illustrative spontaneous examples is given beginner teacher to illustrate students difficulty and explaned the new topic. Clarified spontaneous examples is given beginner teacher to clarified students difficulty and students error. Confirmatory spontaneous examples is given beginner teacher to confirm mathematics concept and understanding of students contents.Abstrak: Penelitian ini bertujuan untuk mengeksplorasi karakterisasi contoh spontan guru dalam pembelajaran matematika. Jenis penelitian yang digunakan yaitu kualitatif deskriptif, dengan subjek penelitian guru matematika pemula. Hasil penelitian menunjukan bahwa tiga karakterisasi contoh spontan guru pemula yaitu contoh spontan ilustratif, contoh spontan klarifikatif dan contoh spontan konfirmatif. Contoh spontan ilustratif diberikan guru pemula untuk mengilustrasikan masalah kesulitan yang dialami siswa. Contoh spontan klarifikatif diberikan guru pemula untuk mengklarifikasi kesalahan siswa. Contoh spontan konfirmatif diberikan guru pemula untuk mengonfirmasi bahwa siswa telah memahami materi yang dibahas.